Proton pump inhibitor use significantly increases the risk of spontaneous bacterial peritonitis in 1965 patients with cirrhosis and ascites: a propensity score matched cohort study. Issue 6 (30th July 2014) - Min, Y. W.; Lim, K. S.; Min, B.‐H.; Gwak, G.‐Y.; Paik, Y. H.; Choi, M. S.; Lee, J. H.; Kim, J. J.; Koh, K. C.; Paik, S. W.; Yoo, B. C.; Rhee, P.‐L.
Summary Background The risk of spontaneous bacterial peritonitis (SBP) associated with proton pump inhibitor (PPI) use has been raised in cirrhotic patients with ascites. However, this is based on case–control studies, often with a small series. Aim To determine whether PPI use increases the risk of SBP using a large cohort. Methods This retrospective cohort study included 1965 cirrhotic patients with ascites diagnosed between January 2005 and December 2009. The SBP incidence rate was compared between the PPI and non‐PPI groups before and after propensity score matching to reduce the effect of selection bias and potential confounders. Multivariate analysis was conducted to confirm the association of PPI use with SBP. Results After excluding 411 patients, 1554 were analysed. Among them, 512 patients (32.9%) were included in the PPI group. The annual SBP incidence rate was higher in the PPI group than in the non‐PPI group (10.6% and 5.8%, P = 0.002) before matching. Indications for PPI use and dose of PPI were similar between patients with and without SBP. In the propensity score matched cohort (402 pairs), the SBP incidence rate was also higher in the PPI group than in the non‐PPI group (10.8% vs. 6.0%, P = 0.038). Multivariate analysis revealed that PPI use (Hazard ratio 1.396; 95% confidence interval, 1.057–1.843; P = 0.019) was the independent risk factor for SBP. Conclusions Proton pump inhibitor use significantly increases the risk of spontaneous bacterial peritonitis in cirrhotic patients with ascites. Proton pump inhibitor use should be undertaken with greater caution and appropriately in patients with cirrhosis.